Preserving the Sixties
XVI, 197 p.
Keywords: Re-examining the long-held belief that the Sixties in Britain were dominated mainly by 'youth' and 'protest', the authors in the collection argue that innovation was everywhere shadowed by conservatism. A decade fascinated by itself and, especially, by the future, it also was tormented by self-doubt and accompanied by a fear of losing the past.